Respostas
respondido por:
1
andrezaindria15:
a professora disse que o resultado seria 3 e 7 mas os meus calculos nao dao esse resultado
respondido por:
3
( x - 5 )² = 1
( x - 5 ) . ( x - 5 ) = 1
x² - 5x - 5x + 25 - 1 = 0
x² - 10x + 24 = 0
a = 1
b = - 10
c = 24
x = -b± raíz de b² - 4 . a . c / 2 . a
x = -(-10) ± raíz de (-10)² - 4.1.24 / 2 . 1
x = 10 ± raíz de 100 - 96 / 2
x = 10 ± raíz de 4 / 2
x = 10 ± 2 / 2
x¹ = 10 + 2 / 2 = 12/2 = 6
x² = 10 - 2 / 2 = 8/2 = 4
Solução { 6 , 4 }
( x - 5 ) . ( x - 5 ) = 1
x² - 5x - 5x + 25 - 1 = 0
x² - 10x + 24 = 0
a = 1
b = - 10
c = 24
x = -b± raíz de b² - 4 . a . c / 2 . a
x = -(-10) ± raíz de (-10)² - 4.1.24 / 2 . 1
x = 10 ± raíz de 100 - 96 / 2
x = 10 ± raíz de 4 / 2
x = 10 ± 2 / 2
x¹ = 10 + 2 / 2 = 12/2 = 6
x² = 10 - 2 / 2 = 8/2 = 4
Solução { 6 , 4 }
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás